Effects of Sodium Pump Activity on Spontaneous Firing in Neurons of the Rat Suprachiasmatic Nucleus - Wang, Yi-Chi; Huang, Rong-Chi (Journal of neurophysiology, 2006)
Department of Physiology and Pharmacology, Chang Gung University School of Medicine, Tao-Yuan, Taiwan Submitted 27 December 2005; accepted in final form 7 February 2006 Cell-attached and whole cell recording techniques were used to study the effects of electrogenic sodium pump on the excitability of rat suprachiasmatic nucleus (SCN) neurons. Blocking the sodium pump with the cardiac steroid strophanthidin or zero K + increased the spontaneous firing of SCN neurons to different degrees with different recording modes, whereas turning the sodium pump into a nonselective cation channel with the marine toxin palytoxin invariably increased the spontaneous firing to the point of total blockade. Current-clamp recordings indicated that strophanthidin increased the rate of membrane depolarization and reduced the peak afterhyperpolarization potential (AHP), whereas zero K + also increased the rate of depolarization, but enhanced the peak AHP. The dual effect of zero K + was reflected by the biphasic time course of voltage responses to zero K + : an inhibitory phase with enhanced peak AHP and slower firing, followed by a delayed excitatory phase with faster rate of membrane depolarization and faster firing. In the presence of strophanthidin to block the sodium pump, zero K + consistently decreased firing by enhancing the peak AHP. Repetitive applications of K + -free solution gradually turned the biphasic inhibitory-followed-by-excitatory voltage response into a monophasic inhibitory response in cells recorded with the whole cell (but not the cell-attached) mode, suggesting rundown of sodium pump activity. Taken together, the results suggest that spontaneous firing of SCN neurons is regulated by sodium pump activity as well as the AHP, and that sodium pump activity is modulated by intracellular soluble substances subject to rundown under the whole cell conditions. Address for reprint requests and other correspondence: R.-C. Huang, Department of Physiology and Pharmacology, Chang Gung University School of Medicine, 259 Wen-Hwa 1st Road, Kwei-San, Tao-Yuan, Taiwan (E-mail: rongchiatmail.cgu.edu.tw )